VD_FINDINFO Plainte / 2012 / 49 vom 27. November 2012 - VD Tribunal cantonal (2012)
EXÉCUTION DU SÉQUESTRE, PROCÈS-VERBAL DE SÉQUESTRE, QUOTITÉ SAISISSABLE, MINIMUM VITAL | 17 LP, 93 al. 1 LP, 117 CPC (CH)